Organic Anion Transporting Polypeptide 2B1 in Human Fetal Membranes: A Novel Gatekeeper for Drug Transport During Pregnancy? - Ganguly, Esha; Kammala, Ananth Kumar; Benson, Meagan; Richardson, Lauren S.; Han, Arum; Menon, Ramkumar (Frontiers in Pharmacology, 2021)
Current intervention strategies have not been successful in reducing the risks of adverse pregnancy complications nor maternal and fetal morbidities associated with pregnancy complications. Improving pregnancy and neonatal outcomes requires a better understanding of drug transport mechanisms at the feto-maternal interfaces, specifically the placenta and fetal membrane (FM). The role of several solute carrier uptake transporter proteins (TPs), such as the organic anion transporting polypeptide 2B1 (OATP2B1) in transporting drug across the placenta, is well-established. However, the mechanistic role of FMs in this drug transport has not yet been elucidated. We hypothesize that human FMs express OATP2B1 and functions as an alternate gatekeeper for drug transport at the feto-maternal interface. We determined the expression of OATP2B1 in term, not-in-labor, FM tissues and human FM cells (amnion epithelial cell [AEC], chorion trophoblast cell [CTC], and mesenchymal cells) using western blot analyses and their localization using immunohistochemistry. Changes in OATP2B1 expression was determined for up to 48 hours after stimulation with cigarette smoke extract (CSE), an inducer of oxidative stress. The functional role of OATP2B1 was determined by flow cytometry using a zombie violet dye substrate assay. After OATP2B1 gene silencing, its functional relevance in drug transport through the feto-maternal interface was tested using a recently developed feto-maternal interface organ-on-a-chip (OOC) system that contained both FM and maternal decidual cells. Propagation of a drug (Rosuvastatin, that can be transported by OATP2B1) within the feto-maternal interface OOC system was determined by mass spectrometry. FMs express OATP2B1 in the CTC and AEC layers. In FM explants, OATP2B1 expression was not impacted by oxidative stress. Uptake of the zombie violet dye within AECs and CTCs showed OATP2B1 is functionally active. Silencing OATP2B1 in CTCs reduced Rosuvastatin propagation from the decidua to the fetal AEC layer within the feto-maternal interface-OOC model. Our data suggest that TPs in FMs may function as an alternative drug transport system at the feto-maternal interface, a function that was previously thought to be performed exclusively by the placenta. This new knowledge will help improve drug delivery testing during pregnancy and contribute to designing drug delivery strategies to treat adverse pregnancy outcomes.